Prediction of ACL Injuries from Vertical Jump Kinetics in Division 1 Collegiate Athletes - Marisa Pontillo; Shawn M Hines; Brian J Sennett (International Journal of Sports Physical Therapy)
# Background The incidence of ACL injuries continues to rise secondary to an increase in sport participation. Evidence supports the use of force plate testing to quantify kinetics during rehabilitation after injury and recovery; however, there is limited current research regarding if jump kinetics can identify athletes who are at higher risk for injury. Altered kinetics could potentially lead to abnormal force dissipation and resultant injury.